China's Legalization of Domestic Rhino Horn Trade: Traditional Chinese Medicine Practitioner Perspectives and the Likelihood of Prescription - Cheung, Hubert; Mazerolle, Lorraine; Possingham, Hugh P.; Biggs, Duan (Frontiers in Ecology and Evolution, 2021)
Despite the international ban on the trade of rhino horn that has been in place since 1977, persistent demand for horn in Asia has driven a spike in poaching over the past decade. This has embroiled the conservation community in a debate over the efficacy of banning trade relative to other solutions. Proposals for trade to be legalized and supplied through the dehorning of live rhinos or the production of synthetic horn are contentious. The need for empirical research into the potential impacts of legalization on demand was made more urgent in 2018 when China publicized its intentions to reopen its domestic trade and permit the use of rhino horn in medical treatment. In this study, we interviewed 84 Traditional Chinese Medicine (TCM) practitioners in the Chinese province of Guangdong. While 58 (69.05%, n = 84) of our interviewees were in favor of trade legalization, only 32 (38.10%, n = 84) thought it likely that trade legalization would cause them to increase their prescription of rhino horn over current levels. This is probably because clinical cases in which rhino horn is medically appropriate are uncommon. We also found that 33 (39.29%, n = 84) practitioners were open to using synthetic horn for patient treatment, which has implications for the viability of synthetic horn as a conservation tool. This research contributes empirical insight to advance the discourse on rhino horn trade policy.